Penerapan Metode Membaca Cerita Sains untuk Mengembangkan Literasi pada Siswa Sekolah Dasar Kelas IV - Ayu, Dewi Setiawati Gusti; Nyoman, Tri Wahyuni Ni (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
Currently, Indonesia is facing post-Covid-19 Pandemic conditions. The implementation of the Independent Curriculum is important in the context of post-pandemic learning recovery. In its implementation, the Independent Curriculum emphasizes mastery of minimum competency assessments rooted in the ability to reason using language (literacy). This study aims to describe the development of children's literacy through the science story reading method. This study is a qualitative descriptive study. The subjects of the study were grade IV students of SD Negeri 2 Penatih. Data were obtained through interviews, observations and document studies related to the science story reading method applied in the school. The collected data were then analyzed using the Miles and Huberman Model which consists of the data collection stage, data reduction stage, data presentation stage and conclusion drawing stage and data verification. The results of the study showed that the implementation of the science story reading method consisted of three activities, namely; (1) understanding the meaning of reading stories, (2) understanding story elements and (3) practicing reading stories guided by student worksheets (LKS). The science story reading method applied was able to develop children's literacy. This can be proven through the high level of student interaction in learning and learning outcomes through LKS that were completed well. Through the method of reading science stories, students are invited to practice reasoning about science so that it can later have an impact on increasing their understanding.